(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This study explores the integration of situational contexts into syntactic analysis, with a focus on how specific situations—referred to as partial worlds—influence the truth conditions of utterances in natural language. Building on the theoretical foundations of J.L. Austin’s situational theory, Barwise and Etchemendy’s approach to truth conditions, and Kratzer’s concept of lumps of thought, this paper examines how language encodes events and situations that are dependent on context. Using examples from Nigerian settings, such as card games in Calabar and events in Lagos, we demonstrate that the truth or falsehood of an utterance depends not only on world knowledge but also on the specific partial world it references. Additionally, the study formalizes how tense usage, direct perception reports, and situational dependencies work together to determine the interpretation of utterances within their respective contexts. This framework provides new insights into how syntactic structures and situational semantics can be aligned to account for the complexities of language and meaning, emphasizing the need to consider partial worlds in syntactic analysis for a more nuanced understanding of truth conditions in everyday discourse.